Gibberellic acid, a plant growth regulator, increases mast cell recruitment and alters Substance P levels - ERCAN, FERİHA (ELSEVIER IRELAND LTD, 2008)
Gibberellic acid (GA3), a plant growth regulator, is used commonly in agriculture. its potential hazardous effects on human health. however, were relatively unexplored. Several studies demonstrated that in animals chronic GA3 consumption increased tumor formation and oxidative stress. Mast cells and Substance P(SP) play an important role in inflammation. Because chronic inflammation triggers serious conditions, including tumor formation, we examined changes in mast cell recruitment and activation as well as SP levels in skin and urinary bladder. Wistar Albino rats were treated with either a single GA3 dose or multiple GA3 doses for 30 days. Sub-chronic exposure to GA3 markedly increased mast cell recruitment and activation in both tissues. Treatment with 2 mg/kg GA3 dose for 30 days decreased SP levels in skin and bladder. SP levels returned to control values in bladder and further increased in skin following 30-day treatment with the 20 mg/kg GA3 dose. There was marked urothelial loss and inflammatory cell infiltration in bladder of 30-day GA3 treated groups. In skin, single GA3 doses also decreased SP levels and enhanced mast cell activation and recruitment. Since both SP and mast cell activation elicit inflammatory responses, these results demonstrate that exposure to plant growth regulators may increase inflammatory skin and bladder disease and that use of GA3 should be clearly monitored. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: Plant growth regulators; Gibberellins; Skin; Bladder; Allergy; Inflammation; GENE-RELATED PEPTIDE; NERVE-FIBERS; SKIN; INFLAMMATION; TACHYKININS; CHYMASE; STRESS; DEGRANULATION; ACTIVATION; EXPRESSION